Artifícios dos paraísos - Manganaro, Jean-Paul (Teresa, 2014)
In 1841, Baudelaire’s life was marked by the impossible journey on the ship Paquebot des-Mers-du-Sud. The question is: what influence would it have on the au- thor’s “damned poetry” between “L’Invitation au voyage”, from 1851, and the last poem of “The Flowers of Evil”, “Le voyage,” from 1859?